Menyoroti Sejarah Perkembangan Undang-Undang tentang Air Pengairan dan Sumber Daya Air - Effendi Pasandaran (Forum penelitian Agro Ekonomi, 2015)
EnglishFrom the viewpoint of historical perspective Indonesia has experienced three generations of water law namely Algemeen Water Reglement (general water law), year 1936, Law No 11 of 1974 and Law No 7 Year 2004 on water resources. The purpose of this paper is to study factors considered as the drivers of the emergence of each generation of law. The analysis of historical context identified the dominant factors. The three generations of law are driven by various factors in response to the emerging political interests. In the first, ethical politics, development of hydraulic technology, and the interest to support agricultural export commodity are important driving factors. In the second, green revolution technologies, and the political interest to achieve rice self- sufficiency are dominant factors while that of  the  third is influenced  by politics of bureaucracy  in the aftermath of economic crisis of 1998, economic liberalization as  condition for the World Bank loan, and global political pressure to implement integrated water resources management. By the cancelation of the third generation of law Indonesia is stepping toward the fourth generation of law which has to be prepared in accountable manner based on the principles of good water governance. IndonesianDari perspektif sejarah, Indonesia telah mengalami tiga generasi undang-undang yang terkait dengan air, yaitu Algemene Water Reglement tahun 1936, Undang-Undang No. 11 Tahun 1974 tentang Pengairan, dan UU No. 7 Tahun 2004 tentang Sumber Daya Air. Tulisan ini bertujuan mempelajari faktor-faktor penyebab munculnya undang-undang pada setiap generasi dan mengusulkan langkah-langkah kebijakan untuk mempersiapkan undang-undang generasi keempat. Berdasarkan konteks sejarah diidentifikasi faktor-faktor dominan yang menjadi pemicu munculnya undang-undang pemicu. Ketiga generasi undang-undang tersebut dipicu oleh berbagai faktor sebagai respons terhadap  berbagai kepentingan politik yang muncul. Pada generasi pertama, politik etika, perkembangan teknologi hidrolika, dan kepentingan ekspor komoditas pertanian merupakan faktor-faktor pemicu. Pada generasi kedua, teknologi revolusi hijau dan kepentingan politik mencapai swasembada beras merupakan faktor dominan, sedangkan undang-undang generasi ketiga dipengaruhi oleh perkembangan birokrasi politik pasca krisis ekonomi tahun 1998, liberalisasi ekonomi sebagai persyaratan bantuan Bank Dunia, dan tekanan politik global untuk melaksanakan pengelolaan sumber daya air terpadu. Dengan dibatalkannya undang-undang generasi ketiga, Indonesia memerlukan undang-undang generasi keempat yang perlu disiapkan dengan lebih bertanggung jawab  dan didasarkan pada prinsip-prinsip tata kelola air yang baik.